2003
DOI: 10.1176/appi.ajp.160.2.366
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Eating Disorders and Components of Perfectionism

Abstract: The aspect of perfectionism captured by scores on a subscale measuring concern over mistakes may be particularly associated with eating disorders and not generically predictive of psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
159
1
17

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(195 citation statements)
references
References 29 publications
18
159
1
17
Order By: Relevance
“…Several studies have indicated that the facets of perfectionism are differentially related to eating pathology. 4,27,28 For example, previous studies have found that self-oriented perfectionism is related to anorexic symptoms, whereas socially prescribed perfectionism is related to disordered eating symptoms in general, including bulimic symptoms. 29 Instead of examining the association between different facets of perfectionism and eating disorders, this study examined the association between different facets of disordered eating and a more narrowly defined construct of perfectionism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that the facets of perfectionism are differentially related to eating pathology. 4,27,28 For example, previous studies have found that self-oriented perfectionism is related to anorexic symptoms, whereas socially prescribed perfectionism is related to disordered eating symptoms in general, including bulimic symptoms. 29 Instead of examining the association between different facets of perfectionism and eating disorders, this study examined the association between different facets of disordered eating and a more narrowly defined construct of perfectionism.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] Perfectionism represents a precursor to, and a characteristic of, the acute phases of certain eating disorders. [7][8][9][10] Previous investigations have demonstrated that perfectionism persists after long-term weight recovery from anorexia nervosa (AN), and is present in relatives of women with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Self-oriented perfectionism has been related to ED characteristics such as BD, DT and diet [12]. Likewise, perfectionism has been found to be a predictor of BN [4]. In T1 regression analysis, the mother's perfectionism explained EDs when subclinical syndromes were included, but for more severe EDs (EDNOS), the significant variable was interoceptive awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Someone with this diagnosis is frequently constrained, conforming, obsessional, rigid, and perfectionistic" (p. S69). To demonstrate, we present a vignette of an individual with AN ( Figure 2) drawn from an historical account from 1866 (cited in Brumberg, 1988) to highlight features extensively documented in AN both premorbidly and following weight restoration: cognitive and behavioral rigidity (Anderluh et al, 2003;, perfectionism (Bastiani, Rao, Weltzin, & Kaye, 1995;Bulik et al, 2003;Halmi et al, 2000;Woodside et al, 2002), social withdrawal (Diaz-Marsa, Carrasco, & Saiz, 2000; I. C. Gillberg et al, 1995;Godart et al, 2004;Holliday, Uher, Landau, Collier, & Treasure, 2006;Karwautz, Troop, Rabe-Hesketh, Collier, & Treasure, 2003;Kaye et al, 2004), constriction (Geller, Cockell, Hewitt, Goldner, & Flett, 2000), and harm avoidance (Diaz-Marsa et al, 2000;Klump et al, 2000Klump et al, , 2004. In fact, the reliable presentation of this behavioral and personality cluster has been demonstrated to add to the incremental validity of diagnostic accuracy (Westen & Harnden-Fischer, 2001).…”
Section: Overview Of the Phenotypic Expression Of Anmentioning
confidence: 99%